Efeito do pastoreio de bovinos sobre a estrutura da mata ciliar do arroio espinilho em Sant`Ana do Livramento, RS, Brasil - Araujo, Ana Claudia Bentancor (2010)
The present paper was carried out in two fragments of cilium Forest of Espinilho creek, located in Sant Ana do Livramento, RS state. The study was taken in a fragment of forest, without any cattle for two years, and another one, with cattle on it. The component arborous-bush and the natural regeneration in these two areas were evaluated as well as the relation of them with the environmental variants by means of a Canonic Correspondence Analysis (CCA). To do so, TRANSECTOS were set up, of variable length, distant 60 meters one from another, where there were parts of 20m x 20m for the inventory of the adult forest and subparts of 3.16m x 3.16m, inside the parts, for the inventory of the natural regeneration. In the inventory of the arborousbush vegetation, of the land with cattle and of the land without cattle, 42 and 43 parts were set up, respectively. In these parts all the live and dead subjects with CAP≥15.7cm were sampled. The collected data for the phyto-sociological analysis of the species were: CAP and total length. In the subparts, all the regenerative arborous-bush subjects higher than 0.10m and CAP>15.7cm were measured. In order to compose the matrix of the study data information on the environment of each part were collected: soil collection for the physical analysis and pH, determination of the soil depth, reading of the opening of the tree top, determination of the soil declivity and the stones existing in each land part. To obtain the phyto-sociological parameters, the vegetation data were analyzed using Mata Nativa 2® software. It was also analyzed the distribution of the subject density, which was organized according to the class of diameter and length of those two areas. To analyze the environmental correlations of gradients with the flower composition, CCA was used, using the computer program PC-ORD® for Windows, version 5.0. For the study of the arborous-bush vegetation, it is concluded that there was a higher density of subjects in the area with no cattle and, that the more representative families of both areas were the same ones: Myrtaceae e Anacardiaceae. In the area with cattle, the Ocotea acutifolia got a greater ecological importance while in the area without cattle it was the Ocotea acutifolia. Concerned to the environmental importance in the two areas, it is concluded that Ocotea acutifolia is influenced by higher soil depths, a higher level of clay and lower percentages of stones as well as more sand. It is concluded, from the analysis of regeneration, that the most abundant families were Myrtaceae e Anacardiaceae. The two areas presented a similar number of subjects in natural regeneration. However, it was observed problems of regeneration in both two areas, being these problems possibly related to the fact that the cattle step on the grass and eat the herbs. About the CCA it was noticed that the cattle did not obtain a significant correlation of the environment with the large amount of species while the area without cattle got significant results, indicating that L. molleoides e Blepharocalyx salicifolius are relates with bigger opening of dossal and a high percentage of stones, while Sebastiania commersoniana e Sebastiania brasiliensis are co-related with a lower declivity and a higher level of clay.